Revolutionising higher education: A theoretical discourse on the C-L-E-A-R approach for AI integration - Baskara, FX. Risang (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2023)
Academic discourse increasingly highlights the growing role of generative Artificial Intelligence (AI) tools in higher education. This research paper provides an in-depth theoretical analysis of an innovative methodology, termed the C-L-E-A-R approach, that advocates for a responsible, pedagogically grounded strategy for integrating AI tools into teaching and learning processes. While acknowledging AI's potential to transform education, substantial literature predominantly revolves around practical applications, leaving the theoretical analysis a less-trodden avenue. Thus, this research seeks to fill the gap, applying the lenses of five educational theories: Technological Determinism, Engaged Learning Theory, Constructivist Theory, Authentic Assessment Theory, and Responsible Conduct of Research (RCR) theory, to each phase of the C-L-E-A-R approach, respectively. Significant challenges arise with AI integration, such as issues concerning academic integrity, pedagogical adaptations, and the need for a comprehensive understanding of AI functionalities and limitations. This paper probes these pertinent issues, concurrently exploring the ethical implications of AI usage. Utilising rigorous theoretical exploration, this work offers profound insights into the transformative potential of AI in education, contributing a fresh perspective to the existing body of knowledge. The research unfolds significant implications for higher education stakeholders, underscoring the pivotal role of AI integration and the necessity of adopting comprehensive, theoretically informed approaches for an effective transformation.